Using the gross motor function measure evolution ratio to compare different dosage of hyperbaric treatment with conventional therapies in children with cerebral palsy – could it end the controversy? - Marois, Pierre; Letellier, Guy; Marois, Mikaël; Ballaz, Laurent (Frontiers in Neurology, 2024)
The Gross Motor Function Measure is used in most studies measuring gross motor function in children with cerebral palsy. In many studies, including those evaluating the effect of hyperbaric treatment, the Gross Motor Function Measure variations were potentially misinterpreted because of the lack of control groups. The Gross Motor Function Measure Evolution Ratio (GMFMER) uses historical data from the Gross Motor Function Classification System curves and allows to re-analyse previous published studies which used the Gross Motor Function Measure by considering the natural expected evolution of the Gross Motor Function Measure. The GMFMER is defined by the ratio between the recorded Gross Motor Function Measure score increase and the expected increase attributed to natural evolution during the duration of the study. Objective: The objective of this study is to revisit studies done with different dosage of hyperbaric treatment and to compare the GMFMER measured in these studies with those assessing the effects of various recommended treatments in children with cerebral palsy. Methods: PubMed Searches were conducted to included studies that used the Gross Motor Function Measure to evaluate the effect of physical therapy, selective dorsal rhizotomy, botulinum toxin injection, hippotherapy, stem cell, or hyperbaric treatment. The GMFMER were computed for each group of the included studies. Results: Forty-four studies were included, counting 4 studies evaluating the effects of various dosage of hyperbaric treatment in children with cerebral palsy. Since some studies had several arms, the GMFMER has been computed for 69 groups. The average GMFMER for the groups receiving less than 2 hours/week of physical therapy was 2.51.8 whereas in context of very intensive physical therapy it increased to 10.36.1. The GMFMER of stem cell, selective dorsal rhizotomy, hippotherapy, and botulinum toxin treatment was, 6.05.9, 6.52.0, 13.30.6, and 5.02.9, respectively. The GMFMER of the groups of children receiving hyperbaric treatment were 28.113.0 for hyperbaric oxygen therapy and 29.86.8 for hyperbaric air. Conclusion: The analysis of the included studies with the GMFMER showed that hyperbaric treatment can result in progress of gross motor function more than other recognized treatments in children with cerebral palsy.